2019
DOI: 10.1111/tmi.13197
|View full text |Cite
|
Sign up to set email alerts
|

Gender exploitative and gender transformative aspects of employing Health Extension Workers under Ethiopia's Health Extension Program

Abstract: Objectives To apply a gender lens to Ethiopia's Health Extension Program and the role of Health Extension Workers (HEWs). Methods Interviews with 45 HEWs and four focus group discussions with 14 of the same HEWS from three regions in rural Ethiopia: Afar Region; Tigray Region (Adwa Woreda); and two locations in Southern Nations, Nationalities and People's Region (Aleta Wondo Woreda and Kafa Zone). Two focus group discussions were conducted in Afar Region with 17 Women Extension Workers employed by Afar Pastora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…Within the health facility setting, this social norm persisted, with women and men expressing a preference to interact with health workers of the same gender. These findings resonate with studies conducted in Ethiopia and other countries which found that women prefer interacting with female health professionals rather than males for "intimate care" in both community and health facility settings [54][55][56][57][58][59]. Women reported experiences of discomfort, fear and shame in situations where the patient was seen by a health worker of the opposite gender for diseases affecting the genitalia.…”
Section: [Female] Health Development Army Member and She Won't Be Ablsupporting
confidence: 79%
“…Within the health facility setting, this social norm persisted, with women and men expressing a preference to interact with health workers of the same gender. These findings resonate with studies conducted in Ethiopia and other countries which found that women prefer interacting with female health professionals rather than males for "intimate care" in both community and health facility settings [54][55][56][57][58][59]. Women reported experiences of discomfort, fear and shame in situations where the patient was seen by a health worker of the opposite gender for diseases affecting the genitalia.…”
Section: [Female] Health Development Army Member and She Won't Be Ablsupporting
confidence: 79%
“…47 In a Cochrane review, socio-cultural norms that restrict movement of female CHWs and govern acceptable male-female communications were also identified as barriers to doing their jobs successfully. 48 Jackson et al 49 apply a gender lens to HEP and to the role of HEWs and conclude that by changing gender norms and reducing constraints to gender equality, HEP could have more transformative outcomes not just for HEWs but for the communities they serve. Since the majority of HEWs in Ethiopia are women of reproductive age, providing them with childcare, particularly for when they are away for house visits, could be a step forward in gender transforming their work environment.…”
Section: Discussionmentioning
confidence: 99%
“…HEWs are low in health system hierarchy 34 and they saw their jobs as ‘good for females’, but arguably the litmus test for gender transformative programmes is that HEW employment becomes acceptable as men’s work with attractive employment conditions. 17,35…”
Section: Discussionmentioning
confidence: 99%